Assessment of Differently Abled Student’s Inferiority Complex at School Level in the State of West Bengal, India: An Item Analysis - et al., Ranajit Dhara (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this world, everyone starts their life with some feelings of inferiority. Later success or failure is judged by the ability to adjust the feeling of inferiority to the demands of their life. Normally it requires the control and articulates of one’s inferiority complex in order to achieve a beneficial balance in emotional maturity (Lin, 1997). The present study aims to explore the level of Inferiority Complex of the Differently Abled Students and their opinion about each item of inferiority measuring questionnaire constructed by investigators. The tool was standardized by Reliability. The investigator selected 149 Differently Abled Students from Special and General School in West Bengal. After the analysis and interpretation of their given data, the investigator concludes that the moderate level of Inferiority Complex of the Differently Abled Students. The study also revealed that according to most of the Differently Abled Students, Sometimes Rarely and Not at all opinions gave on most of the Statements.